Traceability and security of stock transactions with blockchain and isogenies of supersingular elliptic curves - Montero Alban, Kevin Giovanni (2025)
In this thesis, we explore the intersection of blockchain technology and supersingular elliptic curve isogeny-based cryptography to address emerging security challenges, particularly in the face of advances in quantum computing. We delve deeper into the mathematical model of both domains, contrasting traceability and security. Through our analysis, we aim to pave the way for future implementations of quantum-resistant schemes, improving the security and resilience of blockchain networks in an ever-evolving digital landscape.